5PSQ-074 COVID-19 vaccines: adverse events after a second dose of Pfizer or Astrazeneca vaccines in healthcare workers who received a first dose of Astrazeneca vaccine. (23rd March 2022) - Andrade, R; Mendes, D; Lobo Alves, M; Falcão, M; Cavaco, P; Soares, J; Viegas, E; Farinha, H; Falcão, F
Abstract : Background and importance: The COVID-19 vaccines have shown excellent safety and efficacy profiles. Healthcare workers (HCW), a priority group for vaccination in Portugal, were probably the first to receive mixed vaccines for COVID-19. A previous study reported more adverse events (AE) after using two different COVID-19 vaccines in adults aged 50 years and older. To our knowledge, there are no data for younger individuals. Aim and objectives: To identify and compare self-reported AE after a second dose of Pfizer or AstraZeneca vaccines in HCW who received a first dose of AstraZeneca vaccine. Material and methods: Prospective, cohort study, including hospital HCW who received a first dose of AstraZeneca vaccine, and a second dose of AstraZeneca (group A) or Pfizer (group B) and completed a pharmacovigilance monitoring plan. Specific local reactions and systemic events were assessed until 10 days after each dose of the vaccine by means of a questionnaire. The data were processed using SPSS 26.0. Results: The study included 247 HCW, mean age 41.7±10.8 years, with 75% being female. Of them, 127 were included in group A and 120 in group B. In group A, 76.4% reported at least 1 AE, with a total of 423 AE and a median of 3 (0–15). In group B, 87.5% reported at least 1 AE, with a total of 594 AE and a median of 5 (0–17). The systemic AE with higher incidence were fatigue, malaise and headache in both groups, and chills for group A and somnolence for group B. We found a statistically significant difference in the occurrence of AE (p<0.05; OR 0.462 (0.234;0.910)) and in the number of AE in both groups (p<0.05). Conclusion and relevance: The reported AE frequency in this study is in agreement with that described by other authors. In this study, HCW receiving a second dose of Pfizer were more likely to have an AE and higher number of AE. There are some limitations, namely, post-vaccination symptom data were self-reported and not verified. Active surveillance should continue to check the vaccines' risk/benefit ratio over time. This safety profile knowledge in younger individuals may contribute to boosting trust in vaccines. References and/or acknowledgements: 1. Shaw RH, Stuart A, Greenland M, Liu X, Van-Tam JSN, Snape MD. Heterologous prime-boost COVID-19 vaccination: initial reactogenicity data. Lancet 2021;397 (10289):2043–6. Conflict of interest: No conflict of interest